Bending quasi-static and fatigue behaviour of Norway spruce wood using experimental approach and FEM analysis - Branko Nečemer; Jure Fakin; Srečko Glodež; Matjaž Šraml; Jernej Klemenc; Gorazd Fajdiga (Case Studies in Construction Materials)
This study presents the experimental and computational investigation of Norway spruce wood's quasi-static and fatigue behaviour under three-point bending loading conditions, temperature of 20 °C and humidity of 65 %. The quasi-static experimental tests were performed for radial and tangential wood fibre orientation, while the fatigue tests were performed only for tangential orientation and evaluated using a conditional two-parametric Weibull's probability density function. A computational model was developed and calibrated in the computational simulation by comparing the mechanical responses in both radial and tangential wood fibre orientation. Furthermore, the computational model was enhanced by incorporating the S – N curve derived from prior experimental fatigue tests. From the results of quasi-static tests, it was obtained that the tangential wood fibre orientations withstand higher strength (for approximately 7 %) than the radial wood fibre orientation. When determining the constitutive material parameters, the inverse optimisation procedure with a Genetic Algorithm showed a deviation between the numerical and experimental responses of 2.06 % for the radial fibre orientation and 2.33 % for the tangential fibre orientation. Based on this finding, the proposed computational model was calibrated and can be used further for the numerical simulations of the bending quasi-static and fatigue behaviour of structural elements made of spruce wood.